2022
DOI: 10.1186/s13256-021-03232-3
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter 2 inhibitor-induced euglycemic diabetic ketoacidosis in a patient with coronavirus disease 2019: a case report

Abstract: Background Sodium–glucose cotransporter 2 inhibitors are among the new-generation oral antihyperglycemic agents that have been used in the treatment of type 2 diabetes mellitus. With the recent coronavirus disease 2019 pandemic and rise of cases in the third wave, diagnosis of life-threatening euglycemic diabetic ketoacidosis may easily be overlooked or missed. Case presentation We present the case of a 37-year-old Malay gentleman with underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Initially, a total of 3370 studies were identified from the databases, and after removing duplicates ( n = 1823), eight studies met the inclusion criteria and were included in this review. These studies consisted of seven case reports and one case series that investigated the incidence of eu-DKA in COVID-19 patients receiving SGLT2 inhibitors[ 14 - 21 ]. The combined study population across these studies comprised 12 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a total of 3370 studies were identified from the databases, and after removing duplicates ( n = 1823), eight studies met the inclusion criteria and were included in this review. These studies consisted of seven case reports and one case series that investigated the incidence of eu-DKA in COVID-19 patients receiving SGLT2 inhibitors[ 14 - 21 ]. The combined study population across these studies comprised 12 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The patients included in the studies were from various countries, including the United States ( n = 3)[ 14 , 18 , 19 ], United Kingdom ( n = 5)[ 15 ], Brazil ( n = 1)[ 16 ], Malaysia ( n = 1)[ 20 ], and Belgium ( n = 2)[ 17 , 21 ]. The reported cases of type 1 diabetes mellitus (T1DM) were observed in the studies conducted in the United Kingdom and Belgium[ 17 , 21 ].…”
Section: Resultsmentioning
confidence: 99%